Pengunaan Blog sebagai Alat Efektif dalam Design Situs untuk Penginapan - Devina Chika Larasati; Mega Marsiswan Putri; Puput Suwarta (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
The use of blogs as a tool in website design for the lodging industry has been a significant research focus in the field of web development. This research aims to explore the effectiveness of using blogs as an integral element in lodging website design. Through a combinative method of case studies, surveys, and prototype testing, this research identifies key factors that influence blog-based site design in improving user experience, interaction, and effectiveness of lodging promotions.